Survival experiences and capabilities of women during Typhoon Yolanda - Asumbrado, Angie D.; Bato, Christine Joy T.; Tañola, Kimberly Mae E.; Orbeta, Rosemarie (2015)
Being a woman presents various challenges and struggles especially in the context of disaster. A qualitative study on the lived experiences of women in Tacloban City during Typhoon Yoilanda was conducted to explore the resources they possess and give meanings to their survival experiences. Using a phenomenological approach, the researchers interviewed six women in which three of them experienced the storm surge while the other three did not. The researchers utilized thematic analysis in analyzing the data and found out that women have resources and capabilities which enabled them to survive disasters on their own, even without the presence and aid of men. The results showed that the participants were able to survive Typhoon Yolanda because they have "lakas ng loob," faith in God and because of their identity as mothers. The lived experiences and survival stories of the participants provide them the opportunity to be heard and therefore offer knowledge and understanding to the institutions tasked to facilitate future programs enhancing the welfare of women.